Woodlands of Antiquity: A millennium of dendrochronological data on forest exploitation and timber economy between the Alps and the Atlantic - Bernhard Muigg; Kristof Haneca; Willy Tegel; Martin Grünewald; Vincent Bernard; Niels Bleicher; François Blondel; Matthias Bolliger; Manuel Broich; Yann Couturier; Sjoerd van Daalen; Marta Domínguez-Delmás; et al. (Proceedings of the National Academy of Sciences, 2025)
The Roman Empire dominated large parts of western and central Europe for over half a millennium, leaving a lasting cultural imprint on the continent. In the densely forested regions north of the Alps, material culture was characterized by the use of wood as a primary raw material. Yet, the drivers behind the Roman timber economy and its impact on woodland exploitation and forest dynamics remain poorly understood. To address this, we investigated a unique collection of 20.397 dendrochronologically dated archaeological woods spanning a millennium of European Antiquity (300 BCE–700 CE). Our results reveal significant increases in exploitation during Roman occupation, with regional differences in onset, intensity, and duration. Due to rising civilian and military demand for wood, Roman logging increasingly extended into primary forests far from settlements, which indicates a significantly improved infrastructure, professionalism, and organization of lumbering. The 3rd century CE marks a tipping point, with sharp declines in wood use and long-distance transport, alongside evidence of overexploitation of old-grown forests (trees aged over 200 y). Late Antiquity is characterized by an overall decline in felling activities during the 4th and 5th centuries and a reestablishment of old-grown forests, manifested by increased tree ages thereafter. These findings demonstrate how Roman imperial expansion fundamentally reshaped woodlands north of the Alps and contribute to the environmental and economic history of European Antiquity.